Strategi Optimalisasi Pelayanan Promosi Kesehatan Berbasis Rumah Sakit: Studi Kasus Di Rumah Sakit Umum Daerah Kota Sawahlunto - Delsa Dezolla; Rahmi Melfa Widodo; Sandra Ilona; Erin Desweni; Elsa Marselinda (Institut Penelitian dan Pengembangan Mandalika Indonesia (IP2MI), 2026)
Hospital-based health promotion services (PKRS) can impact a hospital's image. Although not explicitly impacted, hospitals must take development steps to achieve optimal hospital-based health promotion services. The purpose of this study is to provide a reference for the implementation of PKRS at Sawahlunto Regional Hospital by analyzing existing problems and providing solutions, work plans, and monitoring and evaluation plans. This qualitative study used internal hospital document analysis, retrospective field observations, and critical reflection on the processes and obstacles encountered directly in implementing PKRS at Sawahlunto Regional Hospital. The results indicate that the implementation of hospital-based health promotion services at Sawahlunto Regional Hospital is still suboptimal because the person responsible for implementing PKRS has only recently been established under the name PKRS Unit, the PKRS work program is still limited, and internal problems exist, such as limited human resources, funding, and facilities and infrastructure. Based on this research, it is necessary to optimize PKRS supported by the leadership, owners, staff, and stakeholders in the hope of providing comprehensive health services to the community